2014
DOI: 10.1007/s00394-014-0732-x
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-enriched Spirulina protects INS-1E pancreatic beta cells from human islet amyloid polypeptide-induced apoptosis through suppression of ROS-mediated mitochondrial dysfunction and PI3/AKT pathway

Abstract: Our results showed that Se-SE protects INS-1E cells from hIAPP-induced cell death through preventing ROS overproduction, mitochondrial dysfunction and modulating PI3K/AKT pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…After entering into the hepatocytes, a portion of Cu is being transported to the mitochondria for cytochrome c oxidase incorporation [40]. High levels of Cu can induce the overproduction of ROS [3], which further impairs mitochondrial electron transport and results in mitochondrial dysfunction that is linked to the occurrence of apoptosis [41]. In this study, the rates of apoptotic hepatocytes were higher in the three Cu treatment groups than in the control group.…”
Section: Discussionmentioning
confidence: 55%
“…After entering into the hepatocytes, a portion of Cu is being transported to the mitochondria for cytochrome c oxidase incorporation [40]. High levels of Cu can induce the overproduction of ROS [3], which further impairs mitochondrial electron transport and results in mitochondrial dysfunction that is linked to the occurrence of apoptosis [41]. In this study, the rates of apoptotic hepatocytes were higher in the three Cu treatment groups than in the control group.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, the overexpression of MKP-5 inhibited the PA-induced production of intracellular ROS and its associated genes, P22phox and Nox-4. One recent study found that ROS are able to inhibit PI3K/AKT insulin signaling and mitochondrial function, inducing the apoptosis of islet β-cells [ 54 ]. Similarly, MKP-5 may impair the release of inflammatory factors and the production of ROS, thereby reducing the apoptosis and dysfunction of islet cells under lipotoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The normalizing effects by Spirulina on IL-1β, Nrf2 and γGCLC levels in our study can be exerted by different mechanisms. The protective effects in vivo are generally attributed to the anti-oxidant and free radical scavenging properties of the active ingredient C-phycocyanin [36] Concerning mechanistic studies in vitro Spirulina components have also been shown to reactivate the kinase Akt [37], [38] decrease the expression of HDACs, restore LPS mediated decreases in acetylated levels of histone H3 [39], down-regulate pp38 and upregulate ERK1/2 [40]. In our earlier studies in vitro we showed that active p38 had negative and that ERK1/2 had positive effects of Nrf2 activation [28].…”
Section: Discussionmentioning
confidence: 99%